Xanthohumol Inhibited Mechanical Stimulation-Induced Articular ECM Degradation by Mediating lncRNA GAS5/miR-27a Axis - Zheng, Tiansheng; Zhou, Qingluo; Huang, Jishang; Lai, Jinliang; Ji, Guanglin; Kong, Dechao (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is histopathologically marked by extracellular matrix (ECM) degradation in joint cartilage. Abnormal mechanical stimulation on joint cartilage may result in ECM degeneration and OA development. Matrix metalloproteinase 13 (MMP-13) is one of the catabolic enzyme contributing to the degradation of ECM, and it has become the potential biomarker for therapeutic management of OA. Xanthohumol (XH), a natural occurring prenylflavonoid derived from hops and beer, shows the protective activity against OA development. However, the potential mechanisms still need great efforts. In this article, mechanical stimulation could significantly increase the expression of MMP-13 and lncRNA GAS5 (GAS5) and promoting ECM degradation. These could be effectively reversed by XH administration. Suppressed expression GAS5 ameliorated mechanical stimulation-induced MMP-13 expression. MiR-27a was predicted and verified as a target of GAS5, and overexpression of miR-27a down regulated the expression of MMP-13. Collectively, XH exhibited protective effects against mechanical stimulation-induced ECM degradation by mediating GAS5/miR-27a signaling pathway in OA chondrocytes.